Exclusive Breastfeeding Relationship With The Incidence Of Stunting In Toddlers In The Region Work Of Puskesmas Lohbener - Eleni Kenanga Purbasary; Kitri Hikmawati; Titin Hidayatin; Yanni Yanni (Al-Makki Publisher, 2022)
Stunting is a failure to thrive in children under two years old due to chronic malnutrition. Stunting occurs due to a lack of nutritional intake in children in the first 1000 days of life, namely since the child is still in the womb until the child is two years old. Exclusive breastfeeding is very influential in the process of development and growth in children because breast milk contains substances that support motor intelligence and development. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers in the Lohbener Health Center Work Area. This study uses a descriptive-analytic method with a cross-sectional approach with a retrospective approach. The population of this study was 1258 respondents, sampling using simple random sampling with a total sample of 93 respondents. The research instrument used a checklist sheet and was analyzed using the Chi-Square test. The results of this study showed that of the 93 respondents who had children under five years old >24-69 months who were given exclusive breastfeeding 36 (87.8%) were in the normal category, and those who were not exclusively breastfed had stunting 36 (69.2). %) respondents. The results of data analysis showed that P value = 0.000 (? = 0.0121). This study concludes that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers in the Lohbener Health Center Work Area. Suggestions for further researchers by taking samples of the factors that influence the incidence of stunting.